Ice hockey-specific repeated shuttle sprint test performed on ice should not be replaced by off-ice testing - Legerlotz, K.; Kittelmann, J.; Dietzel, M.; Wolfarth, B.; Böhlke, N. (The Journal of Strength and Conditioning Research, 2022)
Although the importance of sport-specific testing has been stated in various studies, the application of standard tests that are little related to the requirements in competition is still widespread in performance diagnostics. Furthermore, the actual exercise mode in testing often deviates from the exercise mode in competition. The aim of this study was therefore to investigate how the performance in an ice hockey mimicking repeated sprint shuttle test conducted off-ice (RSS) differs from the on-ice performance (RISS). The two performance tests were completed by 21 male junior ice hockey players within one week. Anaerobic fatigue was significantly larger in RISS and did not correlate with RSS, whereas best run, mean run, total run time, turn and fly time, and total times in all three shifts correlated moderately. Although the best and mean run times did not differ, these times were achieved with different strategies depending on the test condition, indicated by significantly different split times. Aerobic fatigue in shift 3 was the only parameter where the off-ice measurement correlated strongly with the on-ice measurement. Our results imply that an off-ice test does not predict on-ice performance with sufficient precision, strongly advocating performance testing in the exercise mode used in competition.